Pendampingan Inkubator Bisnis Mahasiswa melalui Sekolah Wirayudha - Hambali, Hambali; Dayat, M. (Humanist Journal, 2023)
A business student incubator is an organizational unit that provides integrated facilities and infrastructure as well as services to foster new entrepreneurs and grow them into strong and independent entrepreneurs. Therefore, student incubators are expected to play a role in encouraging local and national economic growth and creating a more prosperous society. Yudharta University Pasuruan held the WiraYudha #Gen1 school (School for Entrepreneurial Students of the First Generation Yudharta University). UYP Entrepreneurship has high hopes for students to be able to realize and develop a business or business that is in the planning or under construction stage. In addition, it is hoped that the participants can become the 'Best-Pactice' as an interpretation of successful entrepreneurs that other students can emulate. This activity was attended by students from various study programs and levels within the University of Yudharta Pasuruan, with the theme "Independent, Independent, and Empowered". It is hoped that this activity can be held in a sustainable manner in order to create a millennial generation who is creative and innovative in creating new jobs.